Ultrasound Molecular Imaging of Angiogenesis Using Vascular Endothelial Growth Factor-Conjugated Microbubbles - Wang, Jianjun (Mol Pharm, 2017)
Imaging of angiogenesis receptors could provide a sensitive and clinically useful method for detecting neovascularization such as occurs in malignant tumors, and responses to anti-angiogenic therapies for such tumors. We tested the hypothesis that microbubbles (MB) tagged with human VEGF(121) (MB(VEGF)) bind to the kinase insert domain receptor (KDR) in vitro and angiogenic endothelium in vivo, and that this specific binding can be imaged on a clinical ultrasound system. In this work, targeted adhesion of MB(VEGF) was evaluated in vitro using a parallel plate flow system containing adsorbed recombinant human KDR. There was more adhesion of MB(VEGF) to KDR-coated plates when the amount of VEGF(121) on each MB or KDR density on the plate was increased. MB(VEGF) adhesion to KDR-coated plates decreased with increasing wall shear rate. On intravital microscopic imaging of bFGF-stimulated rat cremaster muscle, there was greater microvascular adhesion of MB(VEGF) compared to that of isotype IgG-conjugated control MB (MB(CTL)). To determine if MB(VEGF) could be used to ultrasonically image angiogenesis, ultrasound imaging was performed in mice bearing squamous cell carcinoma after intravenous injection of MB(VEGF). Ultrasound videointensity enhancement in tumor was significantly higher for MB(VEGF) (17.3±9.7 dB) compared to MB(CTL) (3.8±4.4 dB, n=6, p<0.05). This work demonstrates the feasibility of targeted ultrasound imaging of an angiogenic marker using MB(VEGF). This approach offers a non-invasive bedside method for detecting tumor angiogenesis and could be extended to other applications such as molecular monitoring of therapeutic angiogenesis or anti-angiogenic therapies in cardiovascular disease or cancer.